Bacterial and ciliate biofilm community structure at different spatial levels of a salt lake meta-community. Issue 10 (3rd August 2018) - Kavazos, Christopher R J; Huggett, Megan J; Mueller, Ute; Horwitz, Pierre
Abstract: Meta-communities are assembled along an ecological scale that determines local and regional diversity. Spatial patterns have been detected in planktonic bacterial communities at distances <20 m, but little is known about the occurrence of similar variation for other microbial groups and changes in microbial meta-community assembly at different levels of a meta-community. To examine this variation, the biofilm of eight saline ponds were used to investigate processes shaping diversity within ponds (β) and between ponds (δ). Bacterial and ciliate communities were assessed using ARISA and T-RFLP respectively, while diversity partitioning methods were used to examine the importance of taxonomic turnover and variation partitioning was used to distinguish spatial from environmental determinants. The results show that turnover is important for determining β- and δ-diversity of biofilms. Spatial factors are important drivers of bacterial β-diversity but were unimportant for ciliate β-diversity. Environmental variation was a strong determinant of bacterial and ciliate δ-diversity, suggesting sorting processes are important for assembling pond communities. Determinants of diversity in bacteria are not universal for ciliates, suggesting higher functional redundancy of bacteria or the greater niche breadth of ciliates may be important in discriminating assembly processes between the two organisms. Abstract : Using a rigorous sampling design, we determine the different assembly processes important for bacterial and ciliate communities in a salt lake at various scales of meta-community organisation.